2022
DOI: 10.1029/2021tc007127
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Snapshot of Crustal Breakup Deduced From Seismic Analysis of the Tip of the NW South China Sea

Abstract: Based on a high‐resolution seismic reflection data set, we describe and map rift domains at the tip of the V‐shaped NW‐South China Sea (NW‐SCS) Basin. We compare our rift domain map with seismic refraction, magnetic and gravity field data, and previously mapped Continent‐Ocean Boundaries (COB). We also define and map syn‐breakup sedimentary and magmatic sequences across the sediment‐rich NW‐SCS, which enables us to reconstruct the tectono‐stratigraphic evolution of the area. This work enables us to describe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…Recent data from West Iberia, Newfoundland and the South China Sea reveal the pinching‐out, onlapping and eventual lateral disappearance of the Breakup Sequence towards the loci of continental breakup, where oceanic crust is first formed, as the main seismic‐stratigraphic feature marking continental breakup—see Figure 1c,d in Alves and Cunha (2018), figure 10 in Lei et al (2019), figures 7 and 9 in Zhang et al (2021) and figure 8 in Chao et al (2022). The stratigraphic pinch‐out of Breakup Sequences towards the loci of continental breakup can be gradual or abrupt but is usually difficult to identify when approaching the continental slope.…”
Section: Why Breakup‐related Unconformities Do Not Correlate With Pro...mentioning
confidence: 98%
See 3 more Smart Citations
“…Recent data from West Iberia, Newfoundland and the South China Sea reveal the pinching‐out, onlapping and eventual lateral disappearance of the Breakup Sequence towards the loci of continental breakup, where oceanic crust is first formed, as the main seismic‐stratigraphic feature marking continental breakup—see Figure 1c,d in Alves and Cunha (2018), figure 10 in Lei et al (2019), figures 7 and 9 in Zhang et al (2021) and figure 8 in Chao et al (2022). The stratigraphic pinch‐out of Breakup Sequences towards the loci of continental breakup can be gradual or abrupt but is usually difficult to identify when approaching the continental slope.…”
Section: Why Breakup‐related Unconformities Do Not Correlate With Pro...mentioning
confidence: 98%
“…Recent IODP drilling at the loci of contine nta l breakup of the northern South China Sea, has also demonstrated that single seismic markers (breakup-related unconformities) associated with contine nta l breakup comprise local stratigraphic features, cannot be linked to the protracted opening of the South China Sea, and are relative ly older in the basins located inboard of the IODP drilling sites (Zhao et al, 2016;Lei et al, 2019;Zhang et al, 2021;Chao et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 18 exploration wells, sampling the syn‐rift Paleogene strata and locally reaching the top basement, have been tied to the seismic images (Figures 1b and 2) through synthetic seismograms produced by the China National Offshore Oil Corporation (CNOOC). Previous seismic stratigraphy interpretation in the northern SCS was based on CNOOC's age calibration (Zhou et al., 2018; Hao et al., 2022; Zhao et al., 2021; Chao et al., 2022; Ye et al., 2022).…”
Section: Methodsmentioning
confidence: 99%